A COMPARATIVE STUDY OF FORMATIVE ASSESSMENT TOOLS - Tasaratha Rajan Anamalai; Maizatul Hayati bt Mohamad Yatim (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
The intention of formative assessment tools usage is mainly to assess learning outcomes easily and quickly in a classroom environment. However, the tools need to be accurate and informative for teachers and students. At the end of any learning process, students certainly need to know their level of understanding in the learning process and what are the next steps for them to encounter. However, with increasing numbers of students in a classroom and increasing teaching workload among teachers, the teachers can gain benefits from these tools in assessing the outcomes quickly and more effectively. Formative assessment contributes to the learning process by providing the teachers with feedback on how successful the teaching method is and how well the students understand a particular lesson. This article will discuss the usage of formative assessment tools in education. It describes and reviews several kinds of literature related to alternative ways to assess students using technology transform assessment in the teaching process. The reviews use a comparison technique using twelve-criteria of technology transform assessment using three formative assessment tools available in the market. It is believed that technology transform assessment can bring an enjoyable and engaging assessment environment in the classroom